Educação Inclusiva e o Plano de Desenvolvimento Individual: sentidos produzidos no cotidiano de uma escola de ensino fundamental - Nascimento, Karoline Meleiro do (Universidade Federal de São Carlos, 2025)
This dissertation investigates the meanings attributed to the use of the Individual Development Plan (PDI) in the daily life of a public elementary school—early years—within the municipal education system. This qualitative research was conducted through a case study approach (Lüdke & André, 1986) in a school located in a municipality in the state of São Paulo, Brazil. The main objective was to understand how three regular classroom teachers and one Special Education teacher (responsible for Specialized Educational Assistance – AEE) perceive the practical impact of the PDI on their pedagogical activities. The study analyzed the PDI model adopted by the school, its implementation in different educational settings, the meanings assigned to it by the teachers in terms of its objectives and structure, as well as the limitations and potential of the PDI in the teaching and learning process of students in special education. The findings revealed a critical perception of the document. For most teachers, the PDI is seen as a bureaucratic requirement with little practical impact on their pedagogical routines. Although it is described as a reflective tool, its applicability in the classroom is limited, and it is often completed as a formality rather than as an effective pedagogical support. Only in specialized educational services did the PDI demonstrate slightly greater functionality, allowing for individualized monitoring—though still without significant influence on daily teaching practices.The central criticism lies in the lack of integration between individualized planning and collective pedagogical practices, highlighting the absence of specific training and clear guidelines for its use. Teachers point out that although the PDI is presented in educational policies as a key instrument to ensure the inclusion and learning of students with disabilities, in practice, it functions as an administrative document that does not bring about meaningful changes in school organization or inclusive teaching.The meanings constructed by the teachers suggest that the PDI, instead of serving as a transformative pedagogical tool, reinforces the bureaucratization of teaching work and fails to provide structured support for school inclusion.
Inclusive Education and the Individual Development Plan: meanings produced in the daily life of an elementary school
Keywords: Plano de Desenvolvimento Individual; Educação Inclusiva; Prática Docente; Educação Especial; Individual Development Plan; Inclusive Education; Teaching Practice; Special Education; CIENCIAS HUMANAS::EDUCACAO